Coffee Intake and Cardiovascular Disease: Virtue Does Not Take Center Stage - Montagnana, Martina; Favaloro, Emmanuel J.; Lippi, Giuseppe (Seminars in Thrombosis and Hemostasis, 2012)
Coffee is one of the most popular and heavily consumed beverages worldwide, despite the many different methods of preparation and presentation. The results of several epidemiological studies are suggestive for the existence of a U-shaped relationship between coffee consumption and both cardiovascular events and mortality, whereby a lower risk seems associated with low (i.e., less than one cup per day) or high (i.e., more than or equal to four cups per day) coffee intake, whereas a higher risk is reported for intermediate consumption (i.e., two to four cups per day). Most benefits are evident in individuals with a rapid caffeine metabolizer genotype and a low baseline cardiovascular risk. Benefits have also been differentially associated with consumption of decaffeinated coffee, filtered coffee, coffee consumption during lunchtime or dinner, and when coffee is produced in the Italian style (i.e., by espresso or moka). The leading favorable effects have been attributed to various compounds present in coffee. Thus, chlorogenic acids would be effective in decreasing blood pressure, systemic inflammation, risk of type 2 diabetes, and platelet aggregation, whereas caffeine intake has instead been associated with decreased body weight, as well as with increased flow-mediated dilatation and fibrinolysis.
Keywords: caffeine; coffee; cardiovascular disease; hypertension; endothelial dysfunction